Effect of long‐term prophylaxis in the development of cytomegalovirus‐specific T‐cell immunity in D+/R− solid organ transplant recipients. Issue 5 (27th August 2015) - San‐Juan, R.; Navarro, D.; García‐Reyne, A.; Montejo, M.; Muñoz, P.; Carratala, J.; Len, O.; Fortun, J.; Muñoz‐Cobo, B.; Gimenez, E.; Eworo, A.; Sabe, N.; et al.
Abstract Background This study aimed to characterize the dynamics of acquisition of cytomegalovirus (CMV)‐specific cell‐mediated immunity (CMI) in CMV donor positive/recipient negative solid organ transplant (SOT) patients receiving long‐term antiviral prophylaxis, and to determine whether development of CMI confers protection against CMV disease. Methods A prospective multicenter study was conducted in Spain from September 2009 to September 2012. Whole blood specimens were prospectively collected at 30, 90, 120, 200, and 365 days after SOT, and CMI was determined by enumeration of CMV pp65 and IE‐1‐specific CD69+/interferon‐γ‐producing CD8+ and CD4+ T cells by flow cytometry for intracellular cytokine staining. As part of a simultaneous clinical trial, patients received either early prophylaxis (in the first 3 days after transplantation) in the first period of the study or delayed prophylaxis (initiated at day 14) during the second period of the study. The impact of the dynamics of acquisition of CMV‐specific CMI on the incidence of CMV disease was evaluated by Kaplan–Meier survival analysis. Results A total of 95 SOT recipients were recruited. CMV infection and disease occurred in 38 (40%) and 26 (27.4%) patients, respectively. The proportion of patients achieving any detectable CMV‐specific CMI response at each of the different monitoring points was higher in liver transplant recipients, as compared to kidney or heart transplant recipients. The presence of any detectable response at day 120 or 200 was protective against the development of CMV disease (positive predictive values 92% and 93%, respectively). Conclusions The rate of acquisition of CMV‐specific CMI in SOT recipients undergoing antiviral prophylaxis differed significantly between different SOT populations. Patients developing any detectable CMI response were protected against the occurrence of CMV disease.